Effect of rape flower on benign prostatic hyperplasia in rats - Song-Chan Han; Young-Hak Yun (Universidade de São Paulo, 2022)
Abstract We were carried out to investigate the efficacy of Rape (Rapeseed, Brassica napus L.) flower on BPH (benign prostatic hyperplasia) in rats. We found that the extract from Rape flower prevented hyperplasia in testosterone-induced BPH model, the relevant animal model of human BPH. Extract reduced the weight of prostate and induced significantly cell apoptosis in prostate in BPH model. In addition, the extract controlled expression of TGF-β1 in prostate gland and promoted urinary output in dose-dependence in BPH model. Our data provide that Rape flower may be useful for treatment of BPH.